CROSS CULTURE COMMUNICATION DI PERUSAHAAN TONGKOK - Lusiana, Lusiana; Azizah, Mir'ah (Wen Chuang:Journal of Foreign Language Studies, Linguistics, Education, Literatures, Cultures, and Sinology, 2023)
Intercultural communication (cross cultural communication) is increasingly important in multinational companies in China because of the increasing number of foreign employees working there. This research aims to analyze the intercultural communication challenges that arise in Chinese companies and how to overcome them. The research was conducted through in-depth interviews with 15 foreign employees and 15 Chinese employees who worked in 5 Chinese multinational companies from various industries. The research results show that differences in communication styles, social norms and cultural values often lead to misunderstandings and conflicts between Chinese and foreign employees.Foreign employees often feel Chinese employees are too direct, not open enough and self-centered, while Chinese employees feel foreign employees are too blunt and disrespectful to superiors. Misunderstandings also often occur regarding decision making and problem solving. It is recommended that companies organize cross-cultural training, encourage open communication between departments and a culture of mutual respect to overcome these challenges. Intercultural communication skills need to be trained to all employees so that cooperation and productivity increase.  Keyword: Cross Culture, Communication, Chinese Company